2011
DOI: 10.1177/1359105311405872
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in mothers and fathers of children with severe illnesses

Abstract: Posttraumatic growth (PTG) can occur after various types of trauma but has not been studied prospectively in parents of children with chronic diseases. In this study, PTG was assessed in 126 parents of 67 children with type 1 diabetes or cancer three years after diagnosis. Most parents (62.7%) reported at least a moderate degree of PTG. Quality of family relationships, parental psychological distress and child medical characteristics assessed one month after diagnosis, and parents' gender, explained 34 percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 37 publications
5
66
2
10
Order By: Relevance
“…We identified 17 studies examining PTG in parents of children with pediatric disease 5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (see Table 1), 7 studies that demonstrated PTG or benefit finding in children with pediatric disease [42][43][44][45][46][47][48] (see Table 2), and 2 that included both parents and pediatric patients. 49,50 We summarize the findings from these studies in the nine components of our conceptual model of SPI-PTG: (1) the nature and subjective experience of the traumatic event, (2) trauma and the disruption of a personal worldview, (3) PTG as rebuilding or reshaping this worldview, (4) elements of SPI-PTG, (5) cognitive processing underlying SPI-PTG, (6) affective processing underlying SPI-PTG, (7) posttraumatic afterevents, (8) individual characteristics affecting SPI-PTG, and (9) social support affecting SPI-PTG (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 17 studies examining PTG in parents of children with pediatric disease 5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (see Table 1), 7 studies that demonstrated PTG or benefit finding in children with pediatric disease [42][43][44][45][46][47][48] (see Table 2), and 2 that included both parents and pediatric patients. 49,50 We summarize the findings from these studies in the nine components of our conceptual model of SPI-PTG: (1) the nature and subjective experience of the traumatic event, (2) trauma and the disruption of a personal worldview, (3) PTG as rebuilding or reshaping this worldview, (4) elements of SPI-PTG, (5) cognitive processing underlying SPI-PTG, (6) affective processing underlying SPI-PTG, (7) posttraumatic afterevents, (8) individual characteristics affecting SPI-PTG, and (9) social support affecting SPI-PTG (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…77 Cross-sectional studies suggest that PTSS, which includes intrusive thoughts, avoidance, and hyperarousal, is associated with PTG, and that a certain level of posttraumatic stress (that is, not too much and not too little) likely correlates with PTG. 28,40,49 These studies do not clarify whether posttraumatic stress precedes PTG or is a by-product of the process; PTG can also occur in the absence of posttraumatic stress. [20][21][22] The relation of depression and anxiety to PTG is less clear.…”
Section: Cognitive Processing Underlying Spi-ptgmentioning
confidence: 95%
See 2 more Smart Citations
“…A growing body of recent work has suggested that close relationships can support PTG. Relationship quality, self-disclosure, and support seeking were found to be associated with greater PTG (e.g., Hungerbuehler, Vollrath, & Landolt, 2011;Lindstrom, Cann, Calhoun, & Tedeschi, 2013;Prati & Pietrantoni, 2009). Studies have also shown that partner support can serve as a basis for PTG and PTG-related concepts (e.g., meaning finding) in several loss contexts (Canevello, Michels, & Hilaire, 2016), including parental bereavement POSTTRAUMATIC GROWTH IN BEREAVED PARENTS 7 (Albuquerque, Pereira, & Narciso, 2016;Polatinsky & Esprey, 2000).…”
Section: Interpersonal Factorsmentioning
confidence: 99%